95.8k views
1 vote
What is the solution to the equation -3(h+5)+2=4(h+6)-9

User Pranab
by
6.0k points

2 Answers

1 vote
The answer to your question is h=−4
User Joel Brown
by
6.0k points
1 vote

Answer:


h=-4

Explanation:

The equation is
-3(h+5)+2=4(h+6)-9 we need to find the value of h.

First we are going to distribute the products.


-3(h+5)+2=4(h+6)-9\\ -3h-15+2=4h+24-9\\ -3h-13=4h+15

We have to put the terms with letter h in the left side of the equation and the terms without h in the right side;


-3h-13=4h+15\\ -3h-4h=15+13


-7h=28

Now, for the last step we have to divide both sides of the equation in (-7):


-7h=28\\ ((-7)h)/((-7)) =(28)/((-7)) \\ h=-4

User Mohammad Nadeem
by
5.6k points